2020
DOI: 10.5650/jos.ess20084
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Fatty Acids, Aromatic Compounds and Shelf Life of <i>Paeonia ludlowii</i> Kernel Oil

Abstract: IntroductionIn 1936, the Englishman Ludlow discovered Paeonia ludlowii during his investigation in Tibet. In 1953, he published an article in the British "Botanical Magazine" naming Paeonia ludlowii 1 . It is a deciduous shrub of the genus Paeonia in the family Ranunculaceae, a subspecies of Paeonia delavayi, and it is endemic to Tibet 2 . It is distributed only in a narrow range of approximately 100 km in length in Brahmaputra Canyon at an altitude of 2900 3200 m; it is one of the eight peony species in China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The IP of walnut oil at 110 • C was 0.65 h (data not shown), which deviated from the regression curve and was therefore excluded. Similarly, Zhang et al (44) analyzed the IP of Paeonia ludlowii kernel oil by the OXITEST at 70∼110 • C to extrapolate the shelf-life at room temperature. In that study, good linearity was found over a wide temperature range of 50∼100 • C, suggesting that the OXITEST method depending on oxygen consumption could be time-saving for shelf-life estimations since the oxidation mechanism was not altered at high temperatures (80∼100 • C).…”
Section: Optimization Of the Oxitest Methodsmentioning
confidence: 99%
“…The IP of walnut oil at 110 • C was 0.65 h (data not shown), which deviated from the regression curve and was therefore excluded. Similarly, Zhang et al (44) analyzed the IP of Paeonia ludlowii kernel oil by the OXITEST at 70∼110 • C to extrapolate the shelf-life at room temperature. In that study, good linearity was found over a wide temperature range of 50∼100 • C, suggesting that the OXITEST method depending on oxygen consumption could be time-saving for shelf-life estimations since the oxidation mechanism was not altered at high temperatures (80∼100 • C).…”
Section: Optimization Of the Oxitest Methodsmentioning
confidence: 99%
“…Also, HPLC-MS was used to identify n = 34 metabolites from leaves tentatively. Zhang and coworkers [ 279 ] determined the fatty acid composition of Paeonia ludlowii (Stern & G. Taylor) D.Y. Hong to assess its potential as food.…”
Section: Selected Instrumental Techniques and Their Applicationsmentioning
confidence: 99%
“…Moutan DC., has high ornamental, economic, breeding, medicinal, and development values (Fig. 1) (Hong 1997;Li et al 2018;Li and Wang 2019;Lu et al 2020Lu et al , 2021Zhang et al 2020). Until the end of the twentieth century and the beginning of the twenty-first century, P. ludlowii was listed as an independent species (Hong 1997;Hong and Pan 2005).…”
Section: Introductionmentioning
confidence: 99%